Efficiency of financial markets and algorithmic complexity - Giglio, R; Silva, S da; Gleria, Iram; Ranciaro, A; Matsushita, R; Figueiredo, A (Journal of physics. Conference series, 2010)
In this work we are interested in the concept of market efficiency and its relationship with the algorithmic complexity theory. We employ a methodology based on the Lempel-Ziv index to analyze the relative efficiency of high-frequency data coming from the Brazilian stock market.